Web Design Visual Comic Communication As A Visual Based Learning Media - Ilamsyah, Ilamsyah; Wulandari, Ria; Fahreza, Rivaldy Rifki (Pandawan Sejahtera Indonesia, 2020)
In this era of digitalization, there is no denying that all daily activities are made easier by technological advancements. Not spared from the current learning activities have almost used the progress of digitalization in the delivery of information and learning materials efficiently and effectively. But the more rapid and development of learning methods are not matched by unique creations so that learning becomes boring and can reduce the attractiveness of learning. With the existence of visual communication that has developed, the animation media can be one of the efforts to attract and improve reading and learning, comic animation can be relied upon in the current era where it can cover all groups. The method used in this research is data collection and system design. This web design was created using Yii Framework and Adobe Illustrator. The results of this study aim to improve the quality of learning, making it easier for users to create comics, especially for beginners.